The Effect of Pricing and Promotion on Consumer Purchase Decisions of Suzuki Car at PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru - Mashur Fadli; Meyzi Heriyanto; Lie Othman (Enrichment : Journal of Management, 2021)
This study aims to determine the effect of pricing and promotion on consumer purchasing decisions to determine whether pricing and promotion are effective as a marketing strategy in improving consumer purchasing decisions at Suzuki Car Dealer Companies in Pekanbaru. This study uses quantitative methods with the type of explanatory research, and uses primary data. Data was collected through a questionnaire consisting of 28 questions. The sample consists of 100 consumer respondents from a population of 100 consumers using purposive sampling technique. Research data were collected using a questionnaire that was measured using a Likert scale and processed using multiple regression statistical analysis techniques through SPSS version 25.0. The results of the study found that: 1) Pricing and promotion have a significant effect on consumer purchasing decisions, 2) Pricing has a significant effect on consumer purchasing decisions,3) Promotion has a significant effect on consumer purchasing decisions. The implications of research, pricing and promotion as an effective marketing strategy in improving consumer purchasing decisions, either simultaneously or partially.